Qualidade de sementes de soja convencional e transgênica após colheita e durante armazenamento com e sem controle de temperatura - Senem, Jaqueline (2012)
In a scenario where there is increasing production of soybeans, the quality of the storaging process is a factor of increasing concern, which requires the incorporation of technologies and production systems research in seed companies, adopting measures to ensure the viability of the seed during storage. This study aimed to evaluate the quality of seeds of five soybean cultivars recommended for the Western region of Paraná state, in the South of Brazil, after harvesting and during eight months of storage at different conditions (condition of warehouse, and cold 20 °C ± 2) to determine the effects of storage conditions on the seed, vigor loss and the most resistant cultivars. Evaluations were performed at time 0 (harvest), after the seeds were packaged in multiwall paper. Other evaluations were at 0, 60, 120, 180 and 240 days of storage, through the following tests: germination test in the laboratory, cold test, controlled deterioration, accelerated aging and tetrazolium test. The design was completely randomized factorial (5 x 2), five cultivars and two storage conditions, and results were compared statistically by Tukey test at 5% significance level. The results showed that the CD 202 cultivar had the worst performance from the beginning to the end of storage, being less resistant. The cultivar NK 412 113 was affected drastically in the accelerated aging test after 120 days of storage under both conditions. The cultivars maintained their germination in both environment and cold storage conditions until the end of the cold tests and controlled deterioration. Cultivars CD 233RR and CD 215 were the most vigorous until the end of the storaging process, in the cold chamber and starting at 120 days of storage, the vigor of cultivars CD 202, NK 412113 and NK 7059RR decreased, when subjected to accelerated aging test, indicating lower storage potential. Considering that the germination test is valid for six months, it is concluded that all cultivars showed good performance after two months of shelf life, except the CD 202 cultivar, considering the storage time studied, eight months, it can stated that the cooling storage preserved in better conditions the cultivars CD 215 and CD 233RR until the end of the period and there is no difference in vigor of seeds in terms of being conventional or transgenic.